Philosophical Foundations of Hayk Asatryan’s Ideology - Zakaryan, Seyran (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
Hayk Asatryan (1900-1956), a philosopher, national figure, co-founder of the Taronakanutyun (Taron Nationalist) movement, is one of the prominent figures of Armenian philosophy of the first half of the XX century, who excellently uses philosophy to justify his nationalist ideology. The article presents the following theoretical-philosophical propositions underlying Asatryan’s ideology: a/ he considers the vital questions of the past, present and future of the Armenian nation through the lens of the socio-biological direction of the primordialist theory of ethnology, b/ he also biologizes the cognitive process, viewing it as biological a phenomenon, a mechanism of adaptation to the environment, and sees the truth as a tool for success, c/ Opposing the scientific understanding of the historical development of ethnic communities, he creates a mythical image of the tribe, in which the tribe is considered "the cause and basis of the existence of the nation and the people", moreover, in the formation of the tribal nature, he absolutizes not only hereditary data, but also the role of the natural environment, d/ accepts the existence of a mythical "national spirit", which is inherited through "blood", and the will of God works in the spirit, and in general, "the influence of the spirit gives meaning to every phenomenon of nature and the events of history", e/ analyzing the Armenian historical process and Armenian identity based on historical-philosophical material, making deep conclusions, he considers subjective factors to be the main cause of Armenian failures and tragedies. In order to get out of the created difficult situation, it is proposed to use the nationalist ideology to correct the defects of the identity and transform the "depraved" nature of the nation. If we ignore the outdated and mythical notions about race, spirit, etc., we can say that his lots of ideas and following exhortation remains relevant today: in order to face modern challenges, overcome difficulties and preserve national identity, it is necessary to unite around a national goal and rely on national values.